Microplastics Abundance and Spatial Distribution in Bayinbuluk Alpine Swamp Meadow - Yuxin Tian; Maidinuer Abulaizi; Yunpeng Hu; Yang Hu; Mo Chen; Yuanbin Jia; Tianle Kou; Jianqin Zhou; Hongtao Jia (Agriculture)
In order to investigate the current pollution status and distribution characteristics of soil microplastics (MPs) in Bayinbuluk alpine swamp meadow, soil samples of different depths were collected from the study area. The physicochemical properties of the soil, as well as the abundance and morphological distribution of microplastics, were analyzed. The results showed that the microplastics’ abundance in the samples ranged from 46 to 266 microplastics/kg, with significantly higher levels (p < 0.05) in the 0–10 cm soil layer than in the other layers (10–100 cm). The shapes of microplastics mainly include fibrous, fragmented, thin film, and foamed, and the number of fibrous shapes is significantly higher than the other three types. Microplastic colors included black, yellow, red, blue, green, and clear, with black accounting for 70.16%, significantly more abundant than other colors (p < 0.05). Among the different particle sizes of microplastics, 0.5–1 mm microplastics comprised the largest proportion and were significantly more abundant than other particle sizes. Polyethylene (PE) was found to be a major component of soil microplastics in the study area through random sampling using Raman spectroscopy. Correlation analysis showed that the change in soil layer had a significant effect (p < 0.05) on the number, color, and particle size of microplastics. Meanwhile, an increase in microplastic abundance had a significant effect (p < 0.05) on the soil physicochemical properties. The results of RDA (Redundancy Analysis) and Monte Carlo testing showed that there was a significant correlation between microplastic quantity and soluble organic carbon and soil water content (p < 0.01).